Ketika Allah Tampak dalam Sosok Perempuan: Refleksi atas Perumpamaan Dirham yang Hilang - Reggina, Frisca; Sitorus, Herowati; Prasetiawati; Lukas (Sekolah Tinggi Pastoral Tahasak Danum Pambelum Keuskupan Palangkaraya, 2025)
This paper is concerned with the exploration of women identified with Jesus as an intrinsic part of humanity and as co-workers with God. The life and existence of women in God are women working, loving and at the same time able to struggle within themselves and have the same compassion as men according to Luke 15:8-10. The research method is qualitative research. This qualitative research uses secondary sources, i.e. sources from recent journals, to look at the initiative of God and women in the book of Luke. The results show that women in God are heirs of God's nature, able to forgive, to persevere in all matters of life, to be loved and to love, and also as a metaphor for the salvation of humanity through the parable of the lost Dirham (coin).